2014
DOI: 10.1111/een.12155
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of life history traits of sexual and asexual strains of the parasitoid wasp, Lysiphlebus fabarum (Braconidae: Aphidiinae)

Abstract: 1. This study examined biological characteristics of sexual and asexual strains of the parasitoid wasp, Lysiphlebus fabarum (Marshall) (Hymenoptera: Braconidae).2. Strains were reared in different instar hosts (the black bean aphid, Aphis fabae Scopoli) under identical environmental conditions (21 ∘ C, 65-75% RH, and LD 16:8 h).3. Results showed that the second instar of the aphid is the most suitable growth stage for both strains, as the wasps that emerged from the second instar hosts were larger, more fecund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…individuals investing more in egg production die sooner; Zhang et al 2011;). Tradeoffs at the population level were also suggested, but these were either confounded with parasitoid reproductive mode (sexual vs asexual; Pelosse et al 2007;Ameri et al 2015), or were more likely to represent dif-ferences in the timing of allocation than in total investment (Ellers & van Alphen 1997).…”
Section: Tradeoff Between Eggload and Longevitymentioning
confidence: 99%
“…individuals investing more in egg production die sooner; Zhang et al 2011;). Tradeoffs at the population level were also suggested, but these were either confounded with parasitoid reproductive mode (sexual vs asexual; Pelosse et al 2007;Ameri et al 2015), or were more likely to represent dif-ferences in the timing of allocation than in total investment (Ellers & van Alphen 1997).…”
Section: Tradeoff Between Eggload and Longevitymentioning
confidence: 99%
“…As sexual and asexual lines of L. fabarum are very closely related (Sandrock et al., ), they are generally comparable in terms of generation time and fecundity (Engelstädter, Sandrock, & Vorburger, ). That said, a recent study reported small but significant differences in life‐history traits (e.g., slower development but higher egg number in asexuals), although based on comparing just a single line each (Ameri, Rasekh, & Mohammadi, ).…”
Section: Introductionmentioning
confidence: 99%
“…Body size is strongly correlated with fitness in aphidiine parasitoids, especially in females (e.g. Kant et al ., ), and previous work has shown greater longevity of asexual than sexual females (Ameri et al ., ). We infer that asexual L. fabarum may use superparasitism behaviour to optimise host quality for their progeny.…”
Section: Discussionmentioning
confidence: 97%
“…These strains differ biologically, i.e. asexual females tended to emerge somewhat later than sexual females, but with larger egg loads (Ameri et al, 2015). In the present study, we examined the life-history consequences of two levels of superparasitism in a sexual and an asexual population, and carried out dissections of superparasitised aphids to determine when supernumerary larvae were eliminated.…”
Section: Introductionmentioning
confidence: 99%